Development of a fermented beverage from white mulberry juice using the Kombucha consortium - Hoang Thi Hanh Nhan; Chau Thi Thuy Vy; Nguyen Tiet Minh Nhat; Vu Tran Khanh Linh (Journal of Technical Education Science, 2020)
White mulberry contains various nutrient elements and phytochemicals such as alkaloids, anthocyanins and flavonoids which possess a wide range of biological activities beneficial to human health. In this study, a novel fermented beverage from white mulberry juice was developed using Kombucha tea fungus. Effects of initial sugar concentration, fermentation temperature and recycling number of tea fungus biomass on quality of white mulberry Kombucha were investigated. Results showed that, at initial tea fungus biomass concentration of 100 g/L and initial sucrose concentration of 250 g/L, after 3 days of fermentation at 28oC, the Mulberry Kombucha beverage showed desirable chemical characteristics with an acceptable total acidity content (9.45 g/L), as well as high total polyphenol and vitamin C contents (2099.9 μg/L and 0.51 mg/mL, respectively), giving the beverage a harmonious sweet and sour taste. In addition, the fermentation rate was increased when the tea fungus biomass was repeatedly reused; however, the viability of acetic acid bacteria during sequential tea fungus incubation was lost due to the out number of yeast cells, leading to a drop in total polyphenol and vitamin C contents.